PESAN ALQURAN TENTANG AKHLAK (Analisis Hermeneutis Double Movement Fazlur Rahman Terhadap Q.S. al-Hujurat Ayat 11-13) - Asep Saepul Milah Romli (UIN Siber Syekh Nurjati Cirebon, 2017)
Morals are applications of one's personality. Morals are always a personal reflection of individuals. Regardless of what constitutes a person's background in interacting, morality is always the main focus in assessing behavior. Discussion of morals has become an outdated material that is widely discussed, either directly or simply inserting a small part in the discussion. The discussion about morals that are talked about a lot seems to only end up in the order of the concept without the application. This can be seen from the number of cases that occur. After being examined, everything deviates from moral values. It should be a concern that